Energy analysis of solar powered hydrogen production system with CuO/water nanofluids: An experimental investigation - S. Senthilraja; R. Gangadevi; Hasan Köten; Sivasakthivel Thangavel; M. Baskaran; Mohamed M. Awad (Journal of King Saud University: Engineering Sciences, 2023)
Electrolysis is the process used to produce hydrogen using external electrical energy. Because of less initial and operating cost, less maintenance required, and simple construction, hydrogen production via water electrolysis has gained more attention among users globally. In this current attempt, a novel solar-powered hydrogen generation system was established and tested in different operating circumstances. Throughout the study, nanofluids with concentrations of 0.05%, 0.1%, and 0.2% were utilized, and their effect on electrical performance and hydrogen production rate was examined. Compared to conventional solar panels, the usage of nanofluids resulted in a significant improvement in electrical power productivity and hydrogen output rate. The highest electrical efficiency is with a 0.2% volume fraction of CuO/water nanofluids at 13.5% at Noon. During the same period, the lowest and highest hydrogen yield rates are found for the conventional PV module and 0.2% volume fraction CuO/water nanofluids-based system as 7.9 ml/min and 18.2 ml/min, respectively.